Aid for Trade, Trade Costs and Export Diversification with Reference to Sub-Saharan Africa - Nathoo, Rajiv Kumar (Curtin University, 2019)
Trade costs, which are significantly higher in sub-Saharan Africa (SSA) than in other regions of the world, constitute a potent explanation for the continent’s marginalisation in global trade and its vulnerability to external shocks due to heavy reliance on a few export commodities. This thesis develops a conceptual model to test the hypothesis that Aid for Trade (AfT) can reduce trade costs and spur export diversification in SSA, thereby helping the continent leverage its growth potential through trade.